Peran Kiai Dalam Pembentukan Akhlak Santri Di Pondok Pesantren Miftahul Ulum Mempawah - Imam Subawaihin (Fakultas Tarbiyah IAI Darussalam, 2026)
Pesantren are traditional Islamic educational institutions that remain highly popular among many Indonesians to this day. Students living in pesantren dormitories are not only educated in academic subjects; more importantly, they are also taught to become individuals of good moral character. The kiai plays a crucial role in helping students develop good moral character. The purpose of this study is to examine the role of the kiai in shaping students’ moral character, the methods employed, as well as the supporting and hindering factors in this process. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The findings of this study include the conclusion that the kiai’s role in shaping students’ moral character is profound and comprehensive. Kiai do not view themselves merely as teachers of religious knowledge, but rather as murabbi educators who nurture the soul, shape character, and instill life values in students. The methods used include setting a good example, habit formation, discipline, counseling, and others.